Proportion of urinary tract infection in neonatal sepsis - Ahmed, Parvez; Ashraf, Mohd; Andrabi, Syed Ashiq Nisar; wani, Asma; Bhat, Sayar Ahmed; Mir, Naseer Yousuf (Journal of Pediatric Nephrology, 2021)
Background: Urinary tract infection (UTI) in neonates might be associated with bacteremia and congenital anomalies of the kidney and urinary tract (CAKUT), that in complicated situations can lead to renal parenchymal scarring and chronic kidney disease. Aim: To determine occurrence of UTI in neonatal sepsis. Methods: This cross sectional study was conducted on 500 term, extramural hospitalized neonates, suspected to have infection underwent, a detailed history, physical examination and a comprehensive sepsis workup. The diagnosis of neonatal UTI was based, on positive urine culture, obtained by suprapubic aspiration (SPA). Results: Out of 500 neonates included in our study (324 boys and 176 girls), blood culture was positive in 84 (36.5%) neonates in early-onset sepsis group (n=230), while in late-onset sepsis group (n=270) blood culture was positive in130 (48.1%), p-value < 0.05. In both early-onset sepsis (EOS) and late-onset sepsis (LOS) groups, blood culture was found to be positive in a greater proportion of male (41.3%) than female (29.3%) patients, p-value <0.05. The most common organism isolated from blood and urine culture was Klebsiella, followed by E-coli. Urine culture was positive in 34 (6.8%) patients, among whom 29 (85%) culture-positive cases were from the LOS group, a p-value of <0.05. Conclusions: UTI is not uncommon among the hospitalized neonates, and UTI evaluation among septic neonates can prove beneficial for the prevention of long-term sequelae of neonatal UTI.